Onisimus turgidus (Sars, 1879) (Amphipoda, Uristidae), an overlooked amphipod from sea anemones in Northern Norway - Vader, Wim; Johnsen, Jan Roger; Tandberg, Anne Helene S. (European Journal of Taxonomy, 2020)
Two Norwegian uristid amphipods, obligate associates of sea anemones, have for a long time been confused sub nomine Onisimus normani Sars, 1890. In reality this species only occurs in south Norway, while the north-Norwegian material belongs to O. turgidus (Sars, 1879), described from the Barents Sea and for a long time forgotten. This paper fully illustrates both species, gives a key, and provides data on their distribution and ecology.